Basolateral Amygdala Hyperexcitability Is Associated with Precocious Developmental Emergence of Fear-Learning in Fragile X Syndrome - Cea-Del Rio, C (Society for Neuroscience, 2022)
Fragile X Syndrome is a neurodevelopmental disorder and the most common monogenic cause of intellectual disability, autism spectrum disorders, and anxiety disorders. Loss of fragile x mental retardation protein results in disruptions of synaptic development during a critical period of circuit formation in the BLA. However, it is unknown how these alterations impact microcircuit development and function. Using a combination of electrophysiologic and behavioral approaches in both male (Fmr1-/y) and female (Fmr12/2) mice, we demonstrate that principal neurons in the Fmr1KO BLA exhibit hyperexcitability during a sensitive period in amygdala development. This hyperexcitability contributes to increased excitatory gain in fearlearning circuits. Further, synaptic plasticity is enhanced in the BLA of Fmr1KO mice. Behavioral correlation demonstrates that fear-learning emerges precociously in the Fmr1KO mouse. Early life 4,5,6,7-tetrahydroisoxazolo [5,4-c]pyridin-3ol intervention ameliorates fear-learning in Fmr1KO mice. These results suggest that critical period plasticity in the amygdala of the Fmr1KO mouse may be shifted to earlier developmental time points. Significance Statement In these studies, we identify early developmental alterations in principal neurons in the Fragile X syndrome BLA. We show that, as early as P14, excitability and feedforward excitation, and synaptic plasticity are enhanced in Fmr1KO lateral amygdala. This correlates with precocious emergence of fear-learning in the Fmr1KO mouse. Early life 4,5,6,7-tetrahydroisoxazolo [5,4-c]pyridin-3ol intervention restores critical period plasticity in WT mice and ameliorates fear-learning in the Fmr1KO mouse. Copyright © 2022 the authors.